Diseño y construcción de una máquina tipo descoladora para el cardamomo (2020)
The objective of this research was designed and built a descoladora type machine for cardamom in the company Naturalized Viva NAVICAR S.A, which is located in the urban area of the municipality of Colombia, department of Huila; The design of the machine is made up of a fed hopper in which the dried seed of the industrial oven is poured, so that it can carry out the design using a system of 13 plates per face located in the support coupled to the cylindrical axis; The information gathering procedure started from the measurement of the seed geometry in order to establish the dimensions of the plates, as well as the client's requirements regarding the volume of the process demanded in the company based on the quality of the descolado . Regarding the results obtained, the descoladora machine has an average processing capacity of 120 kg / h.